Strengthening UMKM Human Resources Towards Internationalization - Ritha F Dalimunthe; Ance Marintan D. Sitohang; Aisyah; Darmilisani; Magdalena Linda Sibarani (PT FORMOSA CENDEKIA GLOBAL, 2022)
UMKM have enough role big in development economy national. UMKM are activity capable effort expand field work and give service the wider economy of society. UMKM really need Source Power Qualified human (HR) in face competition business moment this. Qualified human resources and have power global competitiveness to Thing determinant UMKM success. Destination study this is for explore strengthening UMKM human resources towards internationalization. Method used in study this is method exploration descriptive that is with analyze the strategy of empowering UMKM in facing the international market with use review approach or studies library. Research results state that HR is superior could obtained through increasing human resources with good quality education formally or informally. Excellent HR capable manage UMKM with utilize wisdom local, good wisdom tangible and intangible local, so that every UMKM has the uniqueness and advantages of each UMKM. With intelligence and skills possessed by UMKM, UMKM can manage wisdom existing local so that UMKM products can compete in the international market.